Supply Chain Shocks and Retail Resilience: The Dynamics of Global Value Chains and Inventories - Williams, Corey J. M. (Journal of Applied Business and Economics, 2024)
We examine the role and relationship of global value chains and inventories by delving into the dynamic effects of upstream manufacturing shocks on downstream retailer performance. Motivated by the pivotal role inventories play in firm demand management, our research employs a novel two-step methodology involving a reduced-form semiparametric smooth coefficient model, and a structural vector autoregressive model. The findings, based on monthly data spanning from January 1999 to December 2021, reveal a profound, and enduring impact of manufacturing supply chain shocks on the retail sector. Following a unit supply chain shock, downstream retailers experience a substantial and lasting increase in inventory accumulation, accompanied by a short-term decline, and subsequent stabilization in sales. Moreover, post-shock, retailers experience a permanent decrease in output, underscoring the far-reaching, and persistent consequences of disruptions in upstream supply chain agents on downstream retail operations.